Exclosures: An Experimental Technique for Protection of Northern Bobwhite Nests - Joseph H. Treadway Jr.; C. Brad Dabbert; Robert B. Mitchell; Byron R. Buckley (National Quail Symposium Proceedings, 2017)
Nest predation has been implicated as a factor affecting northern bobwhite (Colinus virginianus) recruitment rates. Public stakeholders are increasingly questioning use of lethal methods to manage predation. We evaluated a nonlethal method consisting of single nest treatments using an exclosure to protect nests from potential predators. The exclosure treatment also included use of Amdrot (hydramethylnon) and Snake-a-wayt repellents to deter red-imported fire ants (Solenopsis invicta) and snakes, respectively. We compared nest success of treated (n 1⁄4 8) to untreated nests (n 1⁄4 18). Treated nests were 88% successful which was a 2-fold increase over unprotected nests. We did not observe any difference in hen behavior between treatment and controls. This technique may be useful to study nest success of wild quail and is not intended to be a management technique to influence overall population growth.
Keywords: Amdro; Colinus virginianus; exclosure; fire ants; nest success; non-lethal control; northern bobwhite; predation; Snake-a- way; snakes